Textbook of medical mycology - Jagdish Chander (Jaypee, 2018)
This fourth edition of the Textbook of Medical Mycology is thoroughly revised, updated and enlarged. This has been designed to comprehensively cover the rapid and extensively expanding information in the field of Medical Mycology in a concise, lucid and easily understandable manner. This edition is also incorporating several new reader-friendly features.